2021
DOI: 10.1021/acsenergylett.1c01798
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Symmetry Conversion in Mixed-Halide Hybrid Perovskite upon Illumination

Abstract: Organic−inorganic hybrid halide perovskites (ABX 3 , where A = CH 3 NH 3 + (methylammonium ion, MA); B = Pb 2+ ; and X = Br − , I − , or Cl − ) have excellent optoelectronic properties and are highly efficient photovoltaic materials, but their chemical instability impedes their development for use in next-generation solar cells, wherein they serve as the lightharvesting material. Here, we propose a mechanism of photoluminescence red-shift, a performance-loss phenomenon known as light-induced halide segregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…As illustrated in Figure a,d, the red shift gradually appeared with increasing excitation power density, which agrees well with previous works. , We also demonstrated that there was a threshold of excitation power density for phase segregation, and phase segregation could occur only if the excitation power density was higher than the threshold. ,,, An increase in iodine content was likely to cause lattice mismatches and trigger more defect vacancies, resulting in a smaller threshold . Furthermore, it is worth mentioning that the PL peak position changes two trends: only a red shift (Figure d) or a red shift first and then recovered to the original peak (Figure a), which is consistent with reported research studies. ,,, We repeated the measurements to confirm the reproducibility of the illumination of variable power densities. Both repeated measurement results of two microspheres with different power densities almost coincided (Figure b,e).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As illustrated in Figure a,d, the red shift gradually appeared with increasing excitation power density, which agrees well with previous works. , We also demonstrated that there was a threshold of excitation power density for phase segregation, and phase segregation could occur only if the excitation power density was higher than the threshold. ,,, An increase in iodine content was likely to cause lattice mismatches and trigger more defect vacancies, resulting in a smaller threshold . Furthermore, it is worth mentioning that the PL peak position changes two trends: only a red shift (Figure d) or a red shift first and then recovered to the original peak (Figure a), which is consistent with reported research studies. ,,, We repeated the measurements to confirm the reproducibility of the illumination of variable power densities. Both repeated measurement results of two microspheres with different power densities almost coincided (Figure b,e).…”
Section: Resultssupporting
confidence: 90%
“…51,55 According to the calculation of degrees of freedom, the effective degrees of freedom of Low-PUF and High-PUF are 48 and 52, respectively. Thus, the actual encoding capacity is 2 48 and 2 52 for Low-PUF and High-PUF, respectively. The tiny deviation in the degree of freedom may be attributed to the insufficient number of PUFs.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical calculations in this work using the Vienna ab initio simulation package (VASP 5.0) based on density functional theory (DFT). 42,43 The band structure and density of states were calculated based on CIF files using generalized gradient approximation (GGA) exchange-correlation functional and Perdew-Burke-Ernzerhof (PBE). For related calculations, a 3 Â 3 Â 1 k-point was selected and the cutoff energy was set to 340 eV, the force convergence criterion was 0.01 eV Å À1 .…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The electronic properties of materials are defined by the atomic arrangements and their symmetries, which are analyzed using the crystallographic method. The quantum properties of layered structures in three-dimensional crystals have been studied. Among them, exfoliated nanosheets, such as graphene, , transition metal dichalcogenides (TMD), and layered hydrogen borides, , have attracted wide attention because of their unique properties, including the quantum Hall effect and topological properties …”
mentioning
confidence: 99%